PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI ULANG JASA PRESTIGE BARBERSHOP DI KOTA SABANG DENGAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Rizka Tasya; Bambang Munas Dwiyanto (Faculty of Economics and Business Diponegoro University, 2022)
Along with the times, there is an increase in living standards and lifestyles that make people compete to improve their appearance in terms of hairstyles following the trends. To meet these needs, barbershops have sprung up that offer barber services to specific for men. In Sabang, the barbershop business started around 2020. One of the barbershops with an exclusive nuance is Prestige Barbershop. The target of this business is men who need an attractive appearance. However, Prestige Barbershop is not the only barbershop in Sabang. Various phenomena experienced by Prestige Barbershop, ranging from a decrease in the number of visitors to the receipt of many complaints. Therefore, this study is conducted to examine the effect of quality of services and price on the intention to repurchase Prestige Barbershop services mediated by customer trust. The sampling technique in this study is non-probability sampling with a purposive sampling procedure. A total of 110 respondents were obtained through the distribution of online questionnaires. The respondents used in this study are men who live in Sabang City and have used the services of Prestige Barbershop, then the data were analyzed using the structural equation modeling (SEM) method with the the program of analysis moment of structural (AMOS) version 24. The findings of this study indicate that service quality and price have a positive and significant effect on customer trust. Furthermore, service quality and price have a positive and significant effect on repurchase intention. This study also proves that customer trust mediates the relationship between service quality and price on repurchase intention. Therefore, it can be concluded that all research hypotheses are accepted and are expected to be a reference for Prestige Barbershop in order to increase the trust and repurchase interest of its customers.